2018
DOI: 10.1097/01.aog.0000532937.11462.20
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery after Surgery Implementation in a Cesarean Section Population in an Integrated Healthcare System [35B]

Abstract: INTRODUCTION: Enhanced Recovery After Surgery (ERAS) programs are evidence-based care pathways that focus on optimizing pain control, nutrition, fluids, and mobility. We evaluated implementation of a multi-faceted ERAS program among a cesarean section surgical population within Kaiser Permanente Northern California (KPNC), an integrated healthcare delivery system. We compared process measures before and after ERAS implementation at two pilot hospitals. METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
4
4
0
Order By: Relevance
“…In the current study, ERAS protocol allowed early mobilization in a significantly shorter interval after OR discharge than the control group. The results drawn from this study were in agreement with the results of Lee et al 2018 [16] who found that the early ambulation raised significantly (p 0.001) from 33% to 51% when ERAS protocols were implemented on women undergoing elective CS.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, ERAS protocol allowed early mobilization in a significantly shorter interval after OR discharge than the control group. The results drawn from this study were in agreement with the results of Lee et al 2018 [16] who found that the early ambulation raised significantly (p 0.001) from 33% to 51% when ERAS protocols were implemented on women undergoing elective CS.…”
Section: Discussionsupporting
confidence: 92%
“…This was in agreement with what Lee et al 2018 [16] published earlier that early postoperative resumption of oral intake raised from 17% to 57% (p 0.001) when ERAS protocol was implemented on cases without adverse outcomes, while according to Teoh et al 2007 [17] they found that earlier solid intake resulted in more nausea (10.2 % versus 2 %, with p-value of 0.033), which was self-limiting. Guo et al 2015 [18] published earlier about comparing delayed oral feeding and early oral feeding, they found that early oral feeding promoted a rapid resumption of intestinal sounds, flatus, bowel motion, and regular oral intake (P<0.001 for all) where they stated that "There are no obvious advantages in withholding fluid and food after cesarean.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This difference might be due to the implementation of the intervention and women's wishing to prevent DVT and its manifestations post-cesarean section. This finding was parallel with [36] who stated that early ambulation increased from one third tomore than half in a cesarean section population who attended enhanced recovery after surgery program.…”
Section: Discussionsupporting
confidence: 73%
“…According to the standards of the enhanced recovery after surgery (ERAS) protocol, multimodal analgesic therapy allows for maximum reduction of pain. At the same time, patients stay aware, which increases the chances of early verticalization [ 3 , 4 ]. The main purpose of rapid post-operative verticalization is the prophylaxis of thrombophlebitis, prevention of respiratory and digestive complications, prevention of post-operative adhesions and the improvement of blood supply to tissues [ 5 ].…”
Section: Introductionmentioning
confidence: 99%